Brand Storytelling Usaha Makanan Melalui Singkatan Unik : Spirit Pendidikan Islam Kreatif yang Menggairahkan - Darul Muntaha; Robingun Suyud El Syam; Lukman Nur Amin (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
This article examines food business brand storytelling through a unique acronym: the exciting spirit of creative Islamic education. This paper is set in library research, with inductive analysis. The results of the discussion show that creative and unique food business naming is a brand storytelling strategy in order to attract the hearts of buyers. This strategy can be applied in creative Islamic education to create creative, innovative and fun learning. Research implications: the importance of interdisciplinary research in the future that provides direction for creative Islamic education that compromises contemporary issues. In the Islamic education discourse, education is directed at how children think creatively as a mandate that must be used to the maximum extent possible, without having to lose the essence of religious values. Research is expected to contribute to the field of Islamic education which prioritizes student creativity.